Antimicrobial Activity Of Whey Powder Produced By Non-Thermal Method - RAJESWARY HARI; R. DHANAPPRIYA; M. DECCARAMAN (International Journal of Pharma and Bio Sciences, 2011)
Whey, is a natural product resulting from coagulation of milk. Herein, whey powder prepared by non thermal method, was optimized and investigated for its anti-microbial potential against twelve bacerial isolates belonging to three bacterial species by agar-well diffusion assay. Minimum Inhibitory Concentration values were determined by tissue culture plate method to check the concentration ranges for significant inhibition.From the well diffusion assay, the whey at the concentration of 500mg/ml showed a strong bactericidal activity against all the bacterial isolates, which was almost similar to the commercial antibiotics. The minimum inhibitory concentration for the whey powder was found to be 500 (µg/ml) for nearly six bacterial isolates (E.coli MTCC 1089, E.coli MTCC 1554, E.coli MTCC 1555, S. typhi S005, S. paratyphi S019 and S.paratyphi D420) out of the twelve isolates used in the present study. On the other hand the isolates namely S.paratyphi S 023, Shigella flexneri MTCC 1457 and S. typhi UT 3373, S. tyhpi D 23580 were inhibited at the lower dose of 125µg/ml and 250µg/ml respectively. While the strain E.coli MTCC 82 required about 1000µg/ml of whey powder to attain its Minimum Inhibitory Concentration. The results provide evidence that the whey powder is indeed the potential source of new antibacterial agent which will be helpful for people in the poor community.